2020
DOI: 10.1364/boe.382826
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water diffusion dynamics in corneal phantoms using terahertz time-domain spectroscopy

Abstract: Perturbation of normal corneal water content is a common manifestation of many eye diseases. Terahertz (THz) imaging has the potential to serve as a clinical tool for screening and diagnosing such corneal diseases. In this study, we first investigate the diffusive properties of a corneal phantom using simultaneous THz time-domain spectroscopy (THz-TDS) and gravimetric measurements. We will then utilize a variable-thickness diffusion model combined with a stratified composite-media model to simulate changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Thus, phantoms allow for a more static environment to evaluate corneal hydration sensing methods. Some corneal phantoms are accurately characterized, e.g., contact lenses on metal spheres with a known thickness and water content [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, phantoms allow for a more static environment to evaluate corneal hydration sensing methods. Some corneal phantoms are accurately characterized, e.g., contact lenses on metal spheres with a known thickness and water content [14].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study by Chen et al applied the more appropriate diffusion model to represent water content gradients. 321 Corneal tissue water content gradients have been confirmed in cornea. Castoro et al observed a substantial bound water component in ex vivo bovine corneal samples along the optical axis.…”
Section: Corneal Assessmentmentioning
confidence: 86%
“…Three locations are relevant for coupling a Gaussian beam to aspherical surfaces: at the two solutions to Equation (1), and a third orientation where the corneal apex is coincident with the beam waist. Illuminating the cornea with the beam waist does not produce a curvature match but it's study was motivated results presented in the literature where separate transmitter and receiver paths are coupled through corneal surface at the collocating foci of beams [13], [18]- [20].…”
Section: Surfacesmentioning
confidence: 99%